2005
DOI: 10.1007/s10535-005-5180-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient regeneration of Brassica napus L. hypocotyls and genetic transformation by Agrobacterium tumefaciens

Abstract: An efficient system for shoot regeneration and Agrobacterium-mediated gene transfer into Brassica napus was developed through the modification of the culture conditions. Different concentrations of benzyladenine (1.5, 3.0 and 4.5 mg dm -3 ) and thidiazuron (0.0, 0.15 and 0.30 mg dm -3 ) were evaluated for shoot regeneration of 7, 14 and 21-d-old hypocotyl explants. Maximum shoot regeneration frequency was obtained in 21-d-old explants using 4.5 mg dm -3 benzyladenine and 0.3 mg dm -3 thidiazuron. Under above c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…It was observed that 2 d of pre-cultivation and 2 d of co-cultivation were very effective in producing the highest cucumber regeneration frequency and number of shoots in cucumber. These findings of present study are in agreement with those found by Cardoza and Stewart (2003), Jonoubi et al (2005), Khan et al (2010), Wang et al (2013) and Khan et al (2013). The explants co-cultured for 2 d showed the highest regeneration frequency and number of shoots in current study.…”
Section: Discussionsupporting
confidence: 94%
“…It was observed that 2 d of pre-cultivation and 2 d of co-cultivation were very effective in producing the highest cucumber regeneration frequency and number of shoots in cucumber. These findings of present study are in agreement with those found by Cardoza and Stewart (2003), Jonoubi et al (2005), Khan et al (2010), Wang et al (2013) and Khan et al (2013). The explants co-cultured for 2 d showed the highest regeneration frequency and number of shoots in current study.…”
Section: Discussionsupporting
confidence: 94%
“…In earlier studies, 2,4-D was reported to be an effective growth hormone that produced rapid proliferating friable callus in Curcuma amada [15], Gymnema sylvestris [16] and Brassica napus [17] during in vitro cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that four key factors, seedling age, Agrobacterium concentration, infection time, and co-cultivation time, affect Agrobacterium-mediated transformation as revealed by GUS expression and hygromycin resistance. Previous studies have reported the use of seedlings of different ages from various plant species as donor material for transgenic experiments, including 8-day-old canola seedlings (Maheshwari et al, 2011) and 21-day-old B. napus seedlings (Jonoubi et al, 2005). In the present study, GUS expression and hygromycin resistance were monitored to evaluate the effect of explant age on the transformation frequency of the B. napus 'Precocity'.…”
Section: Optimization Of Factors Affecting Gus Expression and Hygromymentioning
confidence: 97%